(3GdLhgQI GdNGdUI Yf GdThGFH aj GdYbGFO GdeJbheI Ydi LejY GdePGgHs - (3TeS GdOjf YHO GdUeO Hf YHO Gddg GdYdhj GdOGeZGfj,J (B967 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi LejY fYeI HGdcdjI hGdMRFjI MeOkG jcGaF fYeg hHYO aEfc CjgG GdCN GdeMH SCdJfi ai ENJdGa GdCeI ai GdYbGFO hbdJ Ef GdCeQ ETJHg Ydjc abdJ JeSc HGdcJGH GdYRjR s
(3BNQgG (B:s
(3hEYde Cfi eG JcdeJ EdG hbO NHQJ LejY Cgd GdePGgH hdeG VQHJ ai GdYdhe hEQJMdJ dgG ef CcKQ GdCbWGQ JHGYOJ Yf LejY eG ge Ydjg eeG fbe Ydjge hGdSdGe s
(3GdfSNI HgG MhGTs
(3fSNI eUMMIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B10s
Keywords: (3abg GdePGgH GdCNQis